Measuring the carbon dioxide trapped through carbonation after curing of concrete with biochar - Abesamis, Charmille Keith M. (Animo Repository, 2022)
Cement production is responsible for up to 5 to 7% of the world’s carbon dioxide output which results in multiple environmental issues, as such this must be addressed. Although its percentage in the typical proportions of concrete is relatively smaller than the other components, mass production causes a concerning amount of emissions in the atmosphere. As such, the research intended to address the issue by utilizing biochar, an organic matter that has undergone pyrolysis, as a partial replacement to cement. The research used 3%, 6%, and 10% biochar partially replacing cement by weight. Quantification of the carbon dioxide sequestered was done using TGA by calculating the mass loss between two periods of time considering the carbonation that could affect the process. With this, a total of 23 4”x8” concrete cylinder samples were produced that was then cured for 28 days. Strength-related tests were conducted, particularly compressive and split tensile, to verify its capacity to be applied for structural purposes. SEM-EDX analyses for the samples with 0% and 3% biochar were utilized to provide imaging on the surface topography as well as obtain the elemental composition of the biochar and concrete. Based on the data obtained, it was found that the optimal percentage to replace cement with biochar is 3% with a compressive strength of 28.44 MPa indicating its suitability for structural applications. From the TGA tests, it was found that there is an increase on average of 1- 2% in mass loss from pre-carbonation to post-carbonation indicating that lower percentages of biochar reduce the carbonation within the concrete.